2019
DOI: 10.1530/rep-18-0583
|View full text |Cite
|
Sign up to set email alerts
|

Obesity induces ovarian inflammation and reduces oocyte quality

Abstract: In the United States, 36.5% of women between the ages of 20 and 39 years are obese. This obesity results in not only metabolic disorders including type II diabetes and cardiovascular disease, but also impaired female fertility. Systemic and tissue-specific chronic inflammation and oxidative stress are common characteristics of obesity. This is also true in the ovary. Several studies have demonstrated that pro-inflammatory cytokines and reactive oxygen species alter estrous cyclicity, steroidogenesis and ovulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(154 citation statements)
references
References 95 publications
5
146
0
3
Order By: Relevance
“…As this study examined females and diet is known to affect both the estrous cycle 21,22 and oocyte health 23 , and there is mixed evidence for a moderating role of estrous cycle in spatial cognition 24,25 , diet-and microbiomeassociated differences in estrous cycle and oocyte number were investigated. During weeks 1-2 and 6-7, daily estrous monitoring was performed by vaginal lavage.…”
Section: Estrous Cycle Monitoringmentioning
confidence: 99%
“…As this study examined females and diet is known to affect both the estrous cycle 21,22 and oocyte health 23 , and there is mixed evidence for a moderating role of estrous cycle in spatial cognition 24,25 , diet-and microbiomeassociated differences in estrous cycle and oocyte number were investigated. During weeks 1-2 and 6-7, daily estrous monitoring was performed by vaginal lavage.…”
Section: Estrous Cycle Monitoringmentioning
confidence: 99%
“…A growing body of evidence suggests that environmental factors that create stress in the oocytes as well as the periconception stage embryos can have substantial long‐term effects on progeny phenotype. Stressors can include oocyte in vitro maturation medium, embryo culture, medium, maternal low‐protein diet, maternal obesity, diabetes, environmental toxins and chemicals, ethanol consumption, and excess hormonal stimulation (Andreas et al, 2019; Ecker et al, 2004; Eichenlaub‐Ritter & Pacchierotti, 2015; Fleming, Eckert, & Denisenko, 2017; Hart, 2016; L. Li et al, 2020; Mann et al, 2004; Ng, Lau, Yeung, & Ho, 2003; Snider & Wood, 2019; VandeVoort, Grimsrud, Midic, Mtango, & Latham, 2014; Velazquez, 2015). Of particular interest here, is the impact of such factors on the oocyte.…”
Section: Environmental Factors Impacting Long‐term Maternal Effectsmentioning
confidence: 99%
“…Exposure to environmental endocrine disruptors can impact meiosis and oocyte quality and have multi‐generational and transgenerational effects in the ovary (Rattan & Flaws, 2019). Maternal diets deemed unhealthy can lead to mitochondrial dysfunction, inflammation, changes in ER stress and UPR related gene expression ( Atf4, Xbp1s, Hspa1a, Hapa1b ) and reduced developmental competence in ovulated oocytes compared to control litter mates (Boudoures et al, 2017; Ruebel et al, 2017; Snider & Wood, 2019; L. L. Wu et al, 2015). Effects of unhealthy maternal diets have also been observed transgenerationally.…”
Section: Environmental Factors Impacting Long‐term Maternal Effectsmentioning
confidence: 99%
“…We have shown that there are important biochemical differences between mural and cumulus cells [64,65]. Additionally, there have been reports of miRNA differences in poor responders [66] and other genes' expression in cumulus cells from obese women [67,68]; the possibility of mural vs. cumulus differences is on the list for further study.…”
Section: These Findings Have Implications For Ovarian Agingmentioning
confidence: 81%